South Africa's Key Challenges: Tough Choices and New Directions. Issue 1 (March 2014) - Bernstein, Ann
The article looks at the "tough choices" (per the National Development Plan) South Africa has to make to be a successful country. It provides policy recommendations and prescriptions for many of the critical issues facing South Africa. The most urgent policy challenges revolve around high levels of unemployment, the regulation of the labor market and the role of unions, the shortage of skills, and the education system. The solutions proposed include the relaxation of labor laws, which hinder entry into the labor market, especially for young people; the introduction of special economic zones; the adoption of an open migration regime for skilled migrants; and the establishment of low-fee private schools and private tertiary education providers. The article calls for bold and visionary leadership in South Africa to ensure that the "tough choices" needing to be made are implemented.